Diabetes prevention through digital therapy for high-risk individuals: Study protocol for the Malaysia Diabetes Prevention Programme (MyDiPP). - Nurul Fatihah Mohd Fauzi; Sharifah Wajihah Wafa Syed Saadun Tarek Wafa; Naresh Bhaskar Raj; Mohd Ibrahim Abdullah; Norkhairani Abdul Rawi; Nurulhuda Mat Hassan; Rohayah Husain (Malaysian Journal of Nutrition, 2023)
Introduction: Intervention approaches that integrate human coaching into technology are considered as a convenient, accessible and scalable method to reach a larger population at risk. The objective of this paper is to present the protocol for a randomised controlled trial that evaluates the efficacy of a lifestyle intervention programme via a mobile phone app (MyDiPP), which aims to prevent diabetes among adults at risk of developing diabetes. Methods: MyDiPP intervention is to be delivered for 12 months with multiple approaches (weight loss, dietary modification, physical activity, and quality of life). Eligible adults aged 18-65 years, overweight/obese (body mass index, BMI ≥ 23kg/m2), and at high risk of type 2 diabetes [American Diabetes Association (ADA) Diabetes Risk Score ≥5, or haemoglobin A1c (HbA1c) of 5.6-6.2%], will be randomly assigned to one of two study groups (intervention or usual care control groups) in a 1:1 ratio using simple randomisation. Results: Changes in weight and HbA1c level (primary outcomes), and changes in physical activity level, dietary intake, and quality of life (secondary outcomes) will be assessed at 6 and 12 months. Conclusion: This study protocol describes the first digital therapy for diabetes prevention in Malaysia, which will determine whether the effect of this intervention is larger than the effect of usual care in reducing body weight and HbA1c level, and improving dietary intake, physical activity, and quality of life of high-risk individuals. Results from this trial may be useful for preventing type 2 diabetes mellitus in Malaysia.